Oration on the Deceased by the Humble Monk and Presbyter Gregory Tsamblak - Spasova, Maria (Forum Theologicum Sardicense, 2025)
Maria Spasova, Oration on the Deceased by the Humble Monk and Presbyter Gregory Tsamblakus. The translation of Oration on the deceased is made from the earliest copy of the Book of Gregory Tsamblak in MS 31, f. 199 from the Nikiforov collection, RGB, first quarter of 15th century, ff. 20v–52r. Although relatively late, the publication of the homily in modern Bulgarian will provide the Bulgarian reader with a kind of encyclopedia of human being, viewed in the light of the eternal dilemma of life and death that has always occupied human awareness. It testifies to the unquestionable talent of Tsamblak – as an author and to his deep erudition as a theologian, with his unusual exegesis of the main Christian dogmas and the psychological aspects of the human being, figuratively expressed through a sophisticated imagery. This homily proves that Tsamblak rigorously adhered to Orthodoxy in its pure Christian sense and verity.